Organotin(IV) Complexes as Chemotherapeutic Drugs Against Different Types of Cancer Cell Lines: A Review - Erfan, Abeer; Yousif, Emad; Alshanon, Ahmed; El-Hiti, Gamal (Al-Nahrain Journal of Science, 2024)
Recently, organotin(IV) complexes have shown high anticancer activity against various cancer cell lines. They are promising anticancer drugs since they selectively target cancer cells. Complexes’ apoptosis and caspase activities are based on alkyl or aryl groups and the anionic groups in ligands that bind to the metal. Many types of research concentrated on synthesizing different di and tri-organotin complexes using a non-aqueous medium because of its ability to hydrolyze in aqueous solutions. This current work highlights the continuing attempts to synthesize novel organotin complexes using different ligands and evaluate the cytotoxicity against the different cell lines.